IS FLIPPED LEARNING FOR EVERYONE? - Kastuhandani, Fidelis Chosa (PEOPLE: International Journal of Social Sciences, 2016)
An education crisis happens in Indonesia and therefore many policies and efforts are implemented to uplift the quality of its education. The government is committed to improve the infrastructure in the country’s education system so that the students will have better experience in the future. This study analyzes flipped learning as one of the strategies in blended learning that incorporates variety of methods in delivering the content of Lessons in English classroom context. By implementing transcendental phenomenology, this study aims at finding a description on how the students give meaning on the implementation of flipped learning in their Interpreting class. This study tried to capture the narrative description of the students’ lived experience and depicted the emerging themes from the analysis of the students’ understanding, belief, feeling, intention and action. The themes emerged in this study were collaboration, discipline, self-actualization and self-empowerment.